1994
DOI: 10.2337/diacare.17.2.126
|View full text |Cite
|
Sign up to set email alerts
|

Smoking Is Associated With Progression of Diabetic Nephropathy

Abstract: Cigarette smoking represents an important factor associated with progression of nephropathy in treated hypertensive type I diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
135
1
4

Year Published

1995
1995
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 256 publications
(150 citation statements)
references
References 0 publications
10
135
1
4
Order By: Relevance
“…The progression can be delayed by antihypertensive therapy [30], and may be influenced by the quality of metabolic control [31] and protein intake [32]. Recently, an association K. S. L. Lain et al: CholesteroMowering therapy and diabetic nephropathy of smoking with the progression of diabetic nephropathy has also been suggested [33]. The findings of this small study are supportive of a pathogenetic role of hypercholesterolaemia in progressive diabetic glomerular disease.…”
Section: Discussionsupporting
confidence: 56%
“…The progression can be delayed by antihypertensive therapy [30], and may be influenced by the quality of metabolic control [31] and protein intake [32]. Recently, an association K. S. L. Lain et al: CholesteroMowering therapy and diabetic nephropathy of smoking with the progression of diabetic nephropathy has also been suggested [33]. The findings of this small study are supportive of a pathogenetic role of hypercholesterolaemia in progressive diabetic glomerular disease.…”
Section: Discussionsupporting
confidence: 56%
“…Previous studies showed that smoking is an important risk factor for progression of established diabetic nephropathy [32,33]. These findings suggest that the beneficial effect of not smoking is applicable to diabetic patients, especially those with nephropathy.…”
Section: Discussionmentioning
confidence: 82%
“…The impact of cigarette smoking on decline in kidney function in overt diabetic nephropathy in type 1 diabetes has scarcely been studied. Sawicki et al (23) suggested that smoking worsens kidney function as measured by creatinine clearance in a 1-year study of 93 type 1 diabetic patients. However, blood pressure was higher in smokers than in nonsmokers at baseline (148/88 vs. 140/86 mmHg) as well as during follow-up (143/84 vs. 137/85 mmHg).…”
Section: Resultsmentioning
confidence: 99%